1986
DOI: 10.1159/000242515
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Growth Retardation in Rats from Different Levels of Hypoxia

Abstract: Three groups of pregnant Wistar rats were subjected to 3 different levels of hypoxia: 11.6, 10.7 and 9.0%, respectively. Pair-fed and ad libitum fed control groups were included to control for the reduced food intake due to hypoxia. Within the range studied, fetal body weights decreased with decreased oxygen availability. Liver weights were more, brain weights less markedly reduced than body weights. Pair-fed but normally oxygenated animals showed slight reductions in body and organ weights compared to ad libi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
75
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 10 publications
9
75
1
Order By: Relevance
“…Some experimental studies of growth under manipulated O 2 are consistent with the WBE expectations; exposure to chronic hypoxia results in a decrease in adult size in some insects (Klok and Harrison 2009;Harrison et al 2010) as well as reduced growth rates in fish (Wang et al 2009), American alligators Alligator mississippiensis (Owerkowicz et al 2009), and embryonic mammals and birds (de Grauw et al 1986;Giussani et al 2007). For many species, processes like growth respond to hypoxia in a threshold manner and only under extreme conditions (Chabot and Dutil 1999;McNatt and Rice 2004).…”
Section: Testing Growth Models I: Changing Environmentssupporting
confidence: 65%
“…Some experimental studies of growth under manipulated O 2 are consistent with the WBE expectations; exposure to chronic hypoxia results in a decrease in adult size in some insects (Klok and Harrison 2009;Harrison et al 2010) as well as reduced growth rates in fish (Wang et al 2009), American alligators Alligator mississippiensis (Owerkowicz et al 2009), and embryonic mammals and birds (de Grauw et al 1986;Giussani et al 2007). For many species, processes like growth respond to hypoxia in a threshold manner and only under extreme conditions (Chabot and Dutil 1999;McNatt and Rice 2004).…”
Section: Testing Growth Models I: Changing Environmentssupporting
confidence: 65%
“…That the highland mother and fetus are hypoxic relative to lowland pregnancies has been determined in previous investigations (25,32,45,46). Furthermore, experiments in pregnant animals echo the contention that chronic hypoxia without undernutrition during pregnancy can lead to growth retardation in utero (47)(48)(49)(50)(51)(52)(53).…”
Section: Discussionmentioning
confidence: 73%
“…[21][22][23] Studies such as these have reported that chronic fetal hypoxia can program persistent pulmonary hypertension in the newborn and pulmonary hypertension in the adult offspring. 24 However, because maternal exposure to hypoxia can lead to a significant decrease in maternal food intake, 25 the extent to which any adverse effects on the pulmonary circulation of the offspring are due to under-nutrition and/or under-oxygenation, once again, remain unclear.…”
mentioning
confidence: 99%